Qualitative Modeling of Trees Cultivated with Processed Wastewater - Vissikirsky, V. (Індуктивне моделювання складних систем, 2017)
Cultivation of forest trees with processed wastewater is an effective method to reduce the release of harmful substances. For this purpose, the detailed experiments shall be carried out to investigate the ability of trees to absorb chemical elements under increased concentrations in wastewater. The paper considers the development of qualitative modeling tools to support the investigation process. A qualitative inference system shall provide the investigator with qualitative tools showing the complex interactions in a transparent way. Культивация лесных деревьев обработанными сточными водами является эффективным методом уменьшения выбросов вредных веществ. Для этого проводятся детальные эксперименты по изучению способности деревьев поглощать химические элементы при повышенных концентрациях в сточных водах. В работе рассматривается разработка качественных инструментов моделирования для поддержки этого процесса изучения. Система качественного вывода обеспечивает исследователя качественными инструментами, показывая сложные взаимодействия прозрачно. Культивація лісових дерев обробленими стічними водами є ефективним методом зменшення викидів шкідливих речовин. Для цього проводяться детальні експерименти з вивчення здатності дерев поглинати хімічні елементи при підвищених концентраціях у стічних водах. В роботі розглядається розробка якісних інструментів моделювання для підтримки цього процесу вивчення. Система якісного виведення забезпечує дослідника якісними інструментами, показуючи складні взаємодії прозоро.